Value of ezrin, maspin and nm23-H1 protein expressions in predicting outcome of patients with head and neck squamous-cell carcinoma treated with radical radiotherapy. Issue 2 (12th May 2006) - Mhawech-Fauceglia, Paulette; Dulguerov, Pavel; Beck, Amy; Bonet, Marta; Allal, Abdelkarim S
Abstract : Background: Prognostic factors in predicting outcomes in patients with head and neck squamous-cell carcinoma (HNSCC) are limited to the clinical–pathological parameters, including lymph node metastasis, location, grade and stage of the disease. Aim: To determine whether the expression of these proteins has a value in predicting patient outcome. Methods: Ezrin, maspin and nm23-H1 immunohistochemistry in tissue samples of 120 patients with HNSCC were evaluated using the microarray technique. Results: In determining the association among each of the three proteins and the clinical–pathological parameters, low maspin expression was the only one found to be significantly associated with high tumour grade (p = 0.007); all others showed no significant associations. In univariate analysis, patients with tumours expressing high ezrin had a shorter disease-free survival (DFS) of 51% than those with low ezrin expression (DFS 84%; p = 0.08). In multivariate analysis, tumours with the combination of loss of maspin and low histological grade had longer DFS (83%) compared with those with high maspin and high histological grade (DFS 42%; p = 0.08). Conclusion: Our study is the first to determine the value of ezrin and maspin in HNSCC in a large series of patients with long follow-up. Ezrin and maspin seem to have a potential prognostic value in patients with HNSCC but results should be confirmed with further studies.